TABU PERNIKAHAN DALAM BUDAYA BANYUMAS - Rosdiana Puspita Sari; Gigih Ariastuti Purwandari (Universitas Warmadewa, 2024)
Taboo culture is recognized as the culture that is prohibited to do because the doer will receive the bad sanction. This culture exists in many regions in Indonesia for example in Banyumas. Banyumas is one of the regencies in Central Java. This research aims to know the marriage taboo culture in Banyumas. The method that is used is qualitative descriptive so that the data interpretation is not in number or statistical form. The data are taken from the interview to Banyumas society figure and also literature review. The result of this research shows that there are seven marriage taboo cultures in Banyumas society which are ‘misan’ (great-grandchild married to grandchild), the groom has younger kinship than the bride, the spouse who have the similar status in family such as the same grandchild, the spouse whose roof of their house can be seen each other, the inappropriate prediction of birthday calculation of the spouse, the last child who is married to the last child or the first child who is married to the first child and taboo in getting married in Muharam month.